2008
DOI: 10.1038/nm1705
|View full text |Cite
|
Sign up to set email alerts
|

Functional skeletal muscle regeneration from differentiating embryonic stem cells

Abstract: Little progress has been made toward the use of embryonic stem (ES) cells to study and isolate skeletal muscle progenitors. This is due to the paucity of paraxial mesoderm formation during embryoid body (EB) in vitro differentiation and to the lack of reliable identification and isolation criteria for skeletal muscle precursors. Here we show that expression of the transcription factor Pax3 during embryoid body differentiation enhances both paraxial mesoderm formation and the myogenic potential of the cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
384
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(403 citation statements)
references
References 49 publications
14
384
0
5
Order By: Relevance
“…Alternatively, functional myogenic cells can be also derived from embryonic stem cells (ESCs) [34]. Intramuscular and systemic transplantation of Pax3 þ PDGF-aR þ and Flk1 þ ES-derived cells into dystrophic mice results in extensive engraftment of adult myofibers, with enhanced contractile function and no teratoma formation [35]. In order to overcome the immunological problem related to ESCs transplantation, patient-specific induced pluripotent stem (iPS) cells could also be generated [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, functional myogenic cells can be also derived from embryonic stem cells (ESCs) [34]. Intramuscular and systemic transplantation of Pax3 þ PDGF-aR þ and Flk1 þ ES-derived cells into dystrophic mice results in extensive engraftment of adult myofibers, with enhanced contractile function and no teratoma formation [35]. In order to overcome the immunological problem related to ESCs transplantation, patient-specific induced pluripotent stem (iPS) cells could also be generated [36].…”
Section: Discussionmentioning
confidence: 99%
“…Only the latter group showed consistently the ability of giving rise to new fibers and that did not differ to the one injected with SCs derived from C57BL/6 GFP þ mice. While SCs have been isolated according to a well-established protocol [10], we are limited by not using a SC lineage tracing mouse for deriving AFS cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that Pax3, an essential transcription factor for embryonic muscle specification [53][54][55][56], enables the generation of early skeletal muscle progenitors from differentiating mouse embryonic stem cells [57]. Upon local and systemic transplantation into mdx mice, these cells produce substantial engraftment of adult myofibers, which are endowed with superior contractile function [57].…”
Section: Discussionmentioning
confidence: 99%
“…Upon local and systemic transplantation into mdx mice, these cells produce substantial engraftment of adult myofibers, which are endowed with superior contractile function [57]. In order to assess whether Pax3 would enable the reprogramming of adult cells towards the myogenic lineage, we began by extending this approach to a mesenchymal stem cell line (MSCB9) derived from adult mouse bone marrow [39].…”
Section: Discussionmentioning
confidence: 99%
“…As ESCs have high proliferation activity and differentiation potency, they are ideal materials for gene modification (Gropp et al 2003) and regenerative medicine (Darabi et al 2008). Currently, as no bona fide in vitro porcine ESCs are available, porcine iPSCs (PiPSCs) were used as the candidate cells.…”
Section: Introductionmentioning
confidence: 99%